Genomic variations in Mycobacterium tuberculosis from the lungs and blood of HIV-infected individuals in Uganda: insights into compartmentalization. - Nakabuye, Hellen; Aruhomukama, Dickson; Galiwango, Ronald; Kateete, David P. (African Health Sciences, 2024)
Mycobacterium tuberculosis (MTB) clinical strains are relatively varied at the genome level. This in-silico study analyzed genomic differences between MTB isolates from the blood and lungs of TB-HIV positive cohorts in Uganda. The hypothesis was that isolates from the blood have distinct SNPs and INDELs that make them better survivors. Twenty-four MTB-blood and -lung sequences were aligned against the H37Rv reference genome and analyzed using BWA-MEM, IGV, SAMtools, FreeBayes, and SnpEff. Comparative analysis revealed that MTB-blood isolates had 11 virulence genes with distinctive non-synonymous SNPs involved in increasing colony-forming units, lowering host survival, enhancing tissue pathology, and allowing for human host persistence. The majority of INDELs were found in non-virulence genes, with the remainder in both MTB-blood and -lung sequences. The study suggests that MTB-blood isolates have distinctive SNPs that explain their capacity to persist outside of the lungs. However, further research is needed to understand the significance of these SNPs in the pathogenesis of MTB. Mycobacterium tuberculosis (MTB) clinical strains have high genomic variability, and there is a knowledge gap on the genomic differences between MTB isolates from the blood and lungs of TB-HIV positive patients in Uganda. This study found that MTB-blood isolates had 11 virulence genes with distinctive non-synonymous SNPs that may contribute to their capacity to persist outside of the lungs. These findings provide insight into the genomic basis of MTB adaptation in different host environments, but further research is needed to fully understand the significance of these SNPs in MTB pathogenesis.
Keywords: Mycobacterium tuberculosis; Uganda; bioinformatics; genomic variations